Encyclopedia of law and higher education - Russo, Charles J. (A Sage reference publication, 2010)
The Encyclopedia of Law and Higher Education is a compendium of information that tells the story of law and higher education from a variety of perspectives. The editor and contributors place legal issues in perspective so that students of higher education and the law can inform policy makers and practitioners about the meaning and status of the law.